Xanthine Oxidase Inhibitor Febuxostat: Quality Comparisons and Release Kinetic Profile - Saquib M. Qureshi, Farya Zafar, Huma Ali, Shazia Alam, Yusra Shafiq, Sohail Khan, Saba A. Baloch, Kashif Maroof (Journal of Applied Pharmaceutical Science, 2017)
In Asian countries pharmaceutical products of same generic may differ in their quality perspectives. Such moieties offer alternative choices in respective health care deliverance setups with uneven pricing. Rationalizations of such products for prescription selection is mainly dependent of drug fate provided by the manufacturer and mostly suffer comparison details of multisource products. Furthermore drug release behaviour of oral solid dosage forms also significantly important in determining the batch to batch reliability of such formulations. These studies assures the products excellence by discerning different formulations with comparable therapeutic moieties. In the present study quality assessment of four different brands of febuxostat (Test1-Test4) were carried out using various physico-chemical tests. Results were found to be in adequate limits. Also, dissolution profiles of all brands were determined using phosphate buffer pH 6.8. Data was analyzed by several statistical methods as suggested by FDA such as model-dependent, model-independent and one way ANOVA method. Results of one-way ANOVA indicated no significant difference among the release profiles of reference (Test1) and test brands (Test1-Test4) as P values was found to be 0.997. Similarly, results of f1 and f2 indicated that Test1 was found to be similar with the Test2 - Test4. Also all the brands i.e. Test1 - Test4 were found to be best fitted in Weibull model.
Keywords: Febuxostat, Dissolution profiles, Model-dependent, model-independent, Weibull model.